Removal of Methyl Orange Dye from Aqueous Solution Using Electrocoagulation System - Junior, Kalala Kabanza (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Access to freshwater is currently becoming more difficult, primarily as a result of population growth, the expansion of industry, and the lack of regulation over the various effluents in waterways. Wastewater that contains dyes is one of the main environmental hazards to freshwater. Methyl orange is one of the frequently used dyes, and lethal exposure to it can have serious negative effects on one's health and the environment. In the current study, iron and steel electrodes were used to apply an electrocoagulation technique to the removal of the dye methyl orange from aqueous solutions under various conditions. Due to its simplicity, effectiveness, low cost, and lack of excessive chemical use, the electrocoagulation method was adopted. To determine how each parameter affected the dye removal efficiency, variations in the following parameters were examined: pH, initial methyl orange concentration, electrode distances, agitation speed, applied voltage, and electrolyte amount. The results demonstrate that for both iron and steel electrodes, nearly 100% of 20 ppm methyl orange was removed in 20 minutes at pH = 3, electrode distance of 2 cm, electrolyte concentration of 0.75 g, applied voltage of 6 V, and stirring speed of 200 rpm. Additionally, the steel and Fe electrodes used 1.485 kWh and 1.683 kWh of electrical energy, respectively, and showed 62.99% and 79.61 % faraday electrode efficiencies. When the electrical energy used, the cost of the electrodes, and the chemicals to adjust the conductivity are taken into account, the operating costs to treat 1 m3 of aqueous solutions containing 20 ppm of methyl orange were 0.45 USD for iron electrodes and 0.51 USD for steel electrodes. The findings of this study are in line with previously published data that showed that increasing the applied voltage, electrolyte dosage, electrode distance, and pollutant concentration have an impact on the effectiveness of pollutant removal. The findings of this research demonstrate that the electrocoagulation approach can be successfully used to treat dye contaminated water when taking into account removal efficiency, treatment duration, ease of operation, and treatment cost. The generated sludge can also be characterised, modified, and conditioned for further use as an adsorbent or fertiliser.

ÖZ: Özellikle nüfus artışı, endüstrinin genişlemesi ve su yollarındaki çeşitli atık sular üzerinde düzenleme eksikliğinin bir sonucu olarak, tatlı suya erişim şu anda daha zor hale geliyor. Boya içeren atık su, tatlı su için ana çevresel tehlikelerden biridir. Metil turuncu boyası sıklıkla kullanılan boyalardan biridir ve buna ölümcül bir şekilde maruz kalmak kişinin sağlığı ve çevre üzerinde ciddi olumsuz etkilere neden olabilir. Bu çalışmada, çeşitli koşullar altında sulu çözeltilerden metil turuncu boyasının uzaklaştırılmasına bir elektrokoagülasyon tekniği uygulamak için demir ve çelik elektrotlar kullanılmıştır. Basitliği, etkinliği, düşük maliyeti ve aşırı kimyasal kullanımının olmaması nedeniyle elektrokoagülasyon yöntemi benimsenmiştir. Her parametrenin boya çıkarma verimini nasıl etkilediğini belirlemek için şu parametrelerdeki varyasyonlar incelendi: pH, ilk metil turuncu boya konsantrasyonu, elektrot mesafeleri, çalkalama hızı, uygulanan voltaj ve elektrolit miktarı. Sonuçlar, hem demir hem de çelik elektrotlar için, pH = 3, elektrot mesafesi 2 cm, elektrolit konsantrasyonu 0,75 g, uygulanan voltaj 6 V ve 200 rpm karıştırma hızında 20 ppm metil turuncu boyasının yaklaşık %100'ünün 20 dakikada giderildiğini göstermektedir. Ayrıca çelik ve Fe elektrotlar sırasıyla 1.485 kWh ve 1.683 kWh elektrik enerjisi kullanmış, sırasıyla %62.99 ve %84,5 faraday elektrot verimleri göstermiştir. Kullanılan elektrik enerjisi, elektrotların maliyeti ve iletkenliği ayarlayacak kimyasallar göz önüne alındığında, 20 ppm metil turuncu boyası içeren 1 m3 sulu çözeltiyi işlemek için işletme maliyetleri demir elektrotlar için 0,45 USD ve çelik elektrotlar için 0,51 USD olmuştur. Bu çalışmanın bulguları, uygulanan voltajın, elektrolit dozajının, elektrot mesafesinin ve kirletici konsantrasyonunun arttırılmasının kirletici uzaklaştırma etkinliği üzerinde etkisi olduğunu gösteren daha önce yayınlanmış verilerle uyumludur. Bu araştırmanın bulguları, elektrokoagülasyon yaklaşımının, uzaklaştırma verimliliği, arıtma süresi, kullanım kolaylığı ve arıtma maliyeti dikkate alındığında boya ile kirlenmiş suyu arıtmak için başarıyla kullanılabileceğini göstermektedir. Üretilen çamur ayrıca bir adsorban veya gübre olarak daha fazla kullanım için karakterize edilebilir, modifiye edilebilir ve şartlandırılabilir.
Master of Science in Chemistry. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2022. Co-Supervisor: Assoc. Prof. Dr. Akeem Adeyemi Oladipo and Supervisor: Prof. Dr. Mustafa Gazi
Keywords: Thesis Tez; Chemistry Department; Textile dye pollutants; electrocoagulation process; sludge; wastewater treatment